Lassa fever outcomes and prognostic factors in Nigeria (LASCOPE): a prospective cohort study. Issue 4 (April 2021) - Duvignaud, Alexandre; Jaspard, Marie; Etafo, Ijeoma Chukwudumebi; Gabillard, Delphine; Serra, Béatrice; Abejegah, Chukwuyem; le Gal, Camille; Abidoye, Abiodun Tolani; Doutchi, Mahamadou; Owhin, Sampson; Séri, Benjamin; Vihundira, Jackson Katembo; et al.
Summary: Background: Lassa fever is a viral haemorrhagic fever endemic in parts of west Africa. New treatments are needed to decrease mortality, but pretrial reference data on the disease characteristics are scarce. We aimed to document baseline characteristics and outcomes for patients hospitalised with Lassa fever in Nigeria. Methods: We did a prospective cohort study (LASCOPE) at the Federal Medical Centre in Owo, Nigeria. All patients admitted with confirmed Lassa fever were invited to participate and asked to give informed consent. Patients of all ages, including newborn infants, were eligible for inclusion, as were pregnant women. All participants received standard supportive care and intravenous ribavirin according to Nigeria Centre for Disease Control guidelines and underwent systematic biological monitoring for 30 days. Patients' characteristics, care received, mortality, and associated factors were recorded using standard WHO forms. We used univariable and multivariable logistic regression models to investigate an association between baseline characteristics and mortality at day 30. Findings: Between April 5, 2018, and March 15, 2020, 534 patients with confirmed Lassa fever were admitted to hospital, of whom 510 (96%) gave consent and were included in the analysis. The cohort included 258 (51%) male patients, 252 (49%) female patients, 426 (84%) adults, and 84 (16%) children (younger than 18 years). The median time between first symptoms and hospital admission was 8 days (IQR 7–13). At baseline, 176 (38%) of 466 patients had a Lassa fever RT-PCR cycle threshold (Ct) lower than 30. From admission to end of follow-up, 120 (25%) of 484 reached a National Early Warning Score (second version; NEWS2) of 7 or higher, 67 (14%) of 495 reached a Kidney Disease–Improving Global Outcome (KDIGO) stage of 2 or higher, and 41 (8%) of 510 underwent dialysis. All patients received ribavirin for a median of 10 days (IQR 9–13). 62 (12%) patients died (57 [13%] adults and five [6%] children). The median time to death was 3 days (1–6). The baseline factors independently associated with mortality were the following: age 45 years or older (adjusted odds ratio 16·30, 95% CI 5·31–50·30), NEWS2 of 7 or higher (4·79, 1·75–13·10), KDIGO grade 2 or higher (7·52, 2·66–21·20), plasma alanine aminotransferase 3 or more times the upper limit of normal (4·96, 1·69–14·60), and Lassa fever RT-PCR Ct value lower than 30 (4·65, 1·50–14·50). Interpretation: Our findings comprehensively document clinical and biological characteristics of patients with Lassa fever and their relationship with mortality, providing prospective estimates that could be useful for designing future therapeutic trials. Such trials comparing new Lassa fever treatments to a standard of care should take no more than 15% as the reference mortality rate and consider adopting a combination of mortality and need for dialysis as the primary endpoint. Funding: Institut National de la Santé et de la Recherche Médicale, University of Oxford, EU, UK Department for International Development, Wellcome Trust, French Ministry of Foreign Affairs, Agence Nationale de Recherches sur le SIDA et les hépatites virales, French National Research Institute for Sustainable Development.